(untitled) (Journal of Astronomy & Earth Sciences Education, 2020)
Over the last 100 years since the planetarium was invented and began to spread across the planet, discipline-based planetarium education researchers have worked diligently to catalog what concepts are taught in the planetarium and what audiences learn when attending a planetarium show. What is not clearly known is precisely ‘who’ it is that are teaching astronomy in planetaria. Numerous small-scale studies give hints about who plantarians are, but the existing participant demographics provided shed precious little insight about them as broad field of professional experts. Knowing “who planetarians are” is critical to education researchers who need to know when they are studying planetarium educators who are more or less typical of most people in the field and when, instead, they are studying people who are unusual outliers and far less representative of the broader population. As a first step toward obtaining a glimpse of who planetarium educators are, a brief survey was broadly distributed through contemporary social media networks frequented by planetarium educators posing the question, “who are you?” The results from 61 respondents showed that 90% had undergraduate degrees, half of which were in physics or astronomy, and 38% hold graduate degrees. Additionally, only 8% have amateur astronomy or hobbyist backgrounds or any substantive K-12 classroom teaching experience. Perhaps unique to planetarium-based astronomy educators, 38% report having extensive backgrounds in theater and performance, These findings suggest that planetarium educators are a fundamentally different sort of individual than those who teach K-12 astronomy or do outreach as an amateur astronomer and, as such, perhaps have very different professional development requirements and expectations from those other astronomy-education related professional development consumers.